Communication Noise as a Discourse Component - Bigunova, Natalia; Oliinyk, Ganna; Selivanova, Olena (Տիգրան Մեծ)
The paper focuses on the investigation of communicative noise at various levels of monocultural and intercultural communication. Communication noise is seen as a component of a communicative event, functioning as obstacles of different nature that lower the effectiveness of communication, destabilize it and are able to cause communicative conflict or the breakdown of communication. In linguistic pragmat-ics, the main features of communication noise have been identified as vagueness and ambiguity of a mes-sage: vagueness is characterized by a more significant degree of noise than ambiguity. The authors of the article have tried to probe more deeply into the area of communication noise by singling out levels of the communicative situation. The article offers a differentiation of five discourse levels: verbal-semiotic, cog-nitive-interpretational, interactive, ontological and sociocultural levels. The central part of the paper ana-lyzes the barriers that cause communication noise at each of the offered levels of the communicative situa-tion. The raised issues offer prospects for further research, such as investigating of noise effects in real communication, identifying a set of causes leading to communication noise, as well as noise-resistant fac-tors, preventing or removing it.
Keywords: Communication